2020
DOI: 10.1111/jpy.13084
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun metagenomics and microscopy indicate diverse cyanophytes, other bacteria, and microeukaryotes in the epimicrobiota of a northern Chilean wetland Nostoc (Cyanobacteria)

Abstract: Prokaryotic Nostoc, one of the world's most conspicuous and widespread algal genera (similar to eukaryotic algae, plants, and animals) is known to support a microbiome that influences host ecological roles. Past taxonomic characterizations of surface microbiota (epimicrobiota) of free‐living Nostoc sampled from freshwater systems employed 16S rRNA genes, typically amplicons. We compared taxa identified from 16S, 18S, 23S, and 28S rRNA gene sequences filtered from shotgun metagenomic sequence and used microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Vilo et al [23] have reported the identification and the draft genome of a Bacillus bacterium from the microbiota associated with Llayta colonies as a first approach to address physiological relationships within the Llayta microbiome and to gain insights on the survival and adaptive strategies to dryness, arsenic, and UV radiation, among other prevalent extreme environmental conditions at the Andes wetlands. The presence of Anabaena on the resilient microflora accompanying the filamentous Nostoc Llayta was coincident with previous observations reported on Nostoc colonies from Parinacota wetlands [22].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Vilo et al [23] have reported the identification and the draft genome of a Bacillus bacterium from the microbiota associated with Llayta colonies as a first approach to address physiological relationships within the Llayta microbiome and to gain insights on the survival and adaptive strategies to dryness, arsenic, and UV radiation, among other prevalent extreme environmental conditions at the Andes wetlands. The presence of Anabaena on the resilient microflora accompanying the filamentous Nostoc Llayta was coincident with previous observations reported on Nostoc colonies from Parinacota wetlands [22].…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, a different bacterial composition was found at the inner matrix, outer layer, and the littoral zone on Nostoc macrocolonies from Chungará Lake in northern Chile [21]. Comparatively, and using metagenomics, multiple taxonomic markers, and microscopic approaches, Satjarak et al [22] reported high taxonomic diversity (cyanobacteria, microalgae, and anoxygenic bacterial genera) on the accompanying epimicrobiota of macroscopic dark-brown sheets of Nostoc from standing water pools at Parinacota (Lauca National Park, northern Chile).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The natural life cycle of primary producers may involve mutualistic, antagonistic, or commensal interactions with cyanophages, fungi, and heterotrophic bacteria, and positive or negative outcomes have been previously discussed in Nostoc macrocolonies [24][25][26][27]. However, identification of members of the bacterial community associated with edible Llayta macrocolonies have been a pending issue.…”
Section: Introductionmentioning
confidence: 99%